Design and test of a six-rotor unmanned aerial vehicle (UAV) electrostatic spraying system for crop protection - Yanliang, Zhang; Qi, Lian; Wei, Zhang (International Journal of Agricultural and Biological Engineering, 2017)
In recent years, multi-rotor unmanned aerial vehicle (UAV) crop protection operations have experienced tremendous growth. Compared with manual operations, they have advantages such as high operational efficiency, small pesticide dosage, and low pesticide hazards for humans. However, the tiny droplets produced during UAV spraying for crop protection are affected by the rotor air flow and will drift in all directions in an uncontrollable manner, severely affecting the pesticide deposition pattern and resulting in pesticide waste. To improve pesticide use efficiency during multi-rotor UAV spraying, an electrostatic spray system was designed based on electrostatic spray technology and a six-rotor UAV. The proper operation parameters for the UAV electrostatic spray were determined by test, which were spray altitude of 50 cm above the crop, spray pressure of 0.3 MPa and charging voltage of 9 kV. Field test was performed based on these parameters. The results showed that compared with non-electrostatic spray, the electrostatic spray improved by 13.6% in the average deposition density above the sampling device and 32.6% in the middle. The research can provide a reference for designing multi-rotor UAV electrostatic spray devices.Keywords: unmanned aerial vehicle (UAV), multi-rotor, electrostatic spraying, pesticide use efficiency, plant protectionDOI: 10.25165/j.ijabe.20171006.3460Citation: Zhang Y L, Lian Q, Zhang W. Design and test of a six-rotor unmanned aerial vehicle (UAV) electrostatic spraying system for crop protection. Int J Agric & Biol Eng, 2017; 10(6): 68–76.